Evaluation of Rodenticidal Baits Against Rodent Population in Long melon (Cucumis melos var. Utlissimus) Crop Fields - Kumar, Parmesh; Pashan, S C; Sabhlok, V P; Singal, R K (Annals of Arid Zone, 2016)
Single do.se anticoagulant, bromadiolone (0.005%) and acute rodenticide,zinc pho.sphide (2%) were evaluated in long melo.n fields during summer 1994 in and aro.und Hisar. Do.uble baiting treatments comprising zinc phosphide and bromadiolone in different combinations accomplished significantly (P <0.05) higher reduction of rodent population as well as crop damage than that with single baiting treatments conducted with either of the above rodenticides. The deployment o.f different rodenticidal baits resulted in cost-benefit ratio declining between 1:118 and 1:157. The use o.f bro.madio.lo.ne followed by bromadiolone treatment was the most economical